LARVICIDAL AND ENZYME INHIBITORY EFFECTS OF ACALYPHA FRUTICOSA (F.) AND CATHARANTHUS ROSEUS L (G) DON. LEAF EXTRACTS AGAINST CULEX QUINQUEFASCIATUS (SAY.) (DIPTERA: CULICIDAE) - M, Pavunraj; V, Ramesh; S, Sakthivelkumar; V, Veeramani; S, Janarthanan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: The prime objective of this study is to evaluate the larvicidal and enzyme inhibitory effects of Acalypha fruticosa and Catharanthus roseus leaf extracts against Culex quinquefasciatus. Methods: Insecticidal susceptibility tests were carried out using the World Health Organization standard method, and the mortality was observed after 24 hrs exposure. Results: The tested extracts showed a significant larvicidal activity depending on the dose of the plant extracts. However, maximum larval mortality was detected in ethyl acetate extract of A. fruticosa with a lethal concentration (LC50) value of 253.08 ppm and (LC90) value of 455.40 ppm followed by hexane extract of C. roseus with LC50 value of 645.33 ppm and LC90 value of 1452.88 ppm against the larvae of C. quinquefasciatus. In control, there were five different fractions of Î±-carboxylesterases resolved in the gel with the mobilities ranging between 0.14 and 0.66. Î²-carboxylesterase isozyme profile of larvae treated with hexane extract of A. fruticosa showed higher enzyme activities by way of intense staining of fractions both at 1/4 and 1/10 LC50 value of 48 hrs treatments. A. fruticosa ethyl acetate extract, and C. roseus hexane extract exposed larvae indicated increased quantities of Î²-Est4/5 isozymes in the concentration of 1/4 and 1/10 of LC50 value of 24 hrs treatment when compared to control. The protein quantity in the majority of treatments decreased compared to control. Conclusion: The results revealed that the organic leaf extract of A. fruticosa and C. roseus had significant larvicidal and enzyme inhibitory effects against C. quinquefasciatus. Keywords: Acalypha fruticosa, Catharanthus roseus leaves extract, Î²-carboxylesterase, Culex quinquefasciatus, Lethal concentration50.